TEACHERS' AND STUDENTS' PERCEPTIONS ON THE USE OF ENGLISH AS A MEDIUM OF INSTRUCTION: A Survey Study on Pilot International Standard Schools (RSBI) in Bandung - Feisal Aziez, - (2011)
This study is designed to identify: (1) the teachers' and students' perceptions of English as a medium of instruction (EMI), (2) the problems encountered by teachers and students in using EMI, and (3) the factors contributing to the problems in the use of EMI. Some other aspects of the use of EMI were also explored in this study. The respondents consisted of 17 teachers and 182 students from two RSBI (Pilot International Standard School) schools in Bandung, West Java. The study used questionnaire, self-evaluation matrix and interview as the instruments of data gathering. The study revealed that both teachers and students agreed that the internationalization of education in Indonesia was timely, but they contended that subjects were more difficult to master if conveyed through English than through Indonesian. This was considered as the result of the lack of English competence on the part of both teachers and students. The study found out that teachers held confrontational perceptions of their own spoken skill. The factors contributing to the problems were apparently the lack of vocabulary and insufficient grammar competence. Finally, the most preferred solution to the lack of vocabulary is by using Indonesian equivalents and to the lack of grammar is by switching into Indonesian language.